2019
DOI: 10.1038/s41598-019-51666-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation needs and temporal performance differences of gridded precipitation products in peripheral mountain regions

Abstract: Gridded datasets are of paramount importance to globally derive precipitation quantities for a multitude of scientific and practical applications. However, as most studies do not consider the impacts of temporal and spatial variations of included measurements in the utilized datasets, we conducted a quantitative assessment of the ability of several state of the art gridded precipitation products (CRU, GPCC Full Data Product, GPCC Monitoring Product, ERA-interim, ERA5, MERRA-2, MERRA-2 bias corrected, PERSIANN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 62 publications
3
51
0
Order By: Relevance
“…At present, with its long time-series, good spatiotemporal resolution, and large number of parameters available [99], ERA5 is one of the best and complete global-gridded reanalysis meteorological datasets [34,[100][101][102][103]. However, its derived precipitation is still far from "state-of-the-art" conditions [104][105][106][107]. As a result, our validation implicitly showed that dataset resolution is still insufficient to capture precipitation heterogeneity in small catchments by smoothing flood peaks.…”
Section: Resultsmentioning
confidence: 92%
“…At present, with its long time-series, good spatiotemporal resolution, and large number of parameters available [99], ERA5 is one of the best and complete global-gridded reanalysis meteorological datasets [34,[100][101][102][103]. However, its derived precipitation is still far from "state-of-the-art" conditions [104][105][106][107]. As a result, our validation implicitly showed that dataset resolution is still insufficient to capture precipitation heterogeneity in small catchments by smoothing flood peaks.…”
Section: Resultsmentioning
confidence: 92%
“…Usually, the influence of temperature datasets in combination with rainfall datasets is not tested (e.g. Satgé et al, 2019;Camici et al, 2018;Casse et al, 2015;Qi et al, 2016;Zhang et al, 2019), with the exception of a few studies (e.g. Laiti et al, 2018;Lauri et al, 2014), despite the importance of this interaction for evaporation simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Different temperature datasets are used to allow flexibility in rainfall partitioning into evaporation and runoff because temperature is a key variable for the calculation of potential evaporation (Kirchner and Allen, 2020;Zheng et al, 2019;Van Stan et al, 2020). The hydrological model is recalibrated for each of the 102 combinations of rainfall-temperature datasets (Figure 1).…”
Section: Overview Of the Modelling Experimentsmentioning
confidence: 99%
“…Our understanding of environmental systems is underpinned by observational data whose unavailability and uncertainties hinder research and operational applications. Among other factors, atmospheric data quality is of prime importance for the reliability of hydro-meteorological and climatological studies (Ledesma and Futter, 2017;Zandler et al, 2019). Precipitation 35 is one of the major components of the water cycle, which has led to numerous initiatives on understanding its generation, and estimating its amount and variability on Earth (Maidment et al, 2015;Cui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%